Combustion of Lithium Particles in N2—Reaction Rates. Issue 1 (2nd January 2017) - Schiemann, M.; Fischer, P.; Bergthorson, J.; Schmid, G.; Taroata, D.
ABSTRACT: The combustion of single lithium particles ( d p < 200 µm) with N2 was investigated in a laminar flow reactor. A particle sampling probe was used to extract and quench particles at various residence times. Burnout of the extracted particles was analyzed using X-ray diffraction and ultimate analysis (carbon, hydrogen, and nitrogen; CHN) to determine the burnout constituents. The burnout consists mainly of Li3 N and Li as well as some impurities (LiOH, Li2 O, Li2 CO3 ) due to the experimental and analytical procedures. Scanning electron microscopy images report on the structural change of the particles during reaction. The resulting trend of lithium conversion depending on the particle residence time was used to calculate reaction rates for the reaction of lithium particles with nitrogen.